Psychophysiological reactivity, coping behaviour and intrusive memories upon multisensory Virtual Reality and Script-Driven Imagery analogue trauma: A randomised controlled crossover study. (October 2018) - Schweizer, Tina; Renner, Fritz; Sun, Dali; Kleim, Birgit; Holmes, Emily A.; Tuschen-Caffier, Brunna
Highlights: Real-time assessment of peri- and post-traumatic risk factors for stress disorders. Experimental stress induction by a VR and SDI multisensory analogue trauma paradigm. VR and SDI induced trauma-like symptoms in a randomised controlled crossover design. VR induced more trauma-like symptoms than SDI. Both paradigms offer real-time modelling of stress-associated disorders. Abstract: Background: Peri- and post-traumatic factors predict the differential development of stress-associated mental disorders. Prospective designs assessing these risk factors in real-time under controlled experimental conditions can overcome limitations of retrospective designs. Therefore, we aimed to investigate multi-sensory, experimental analogues of a traumatic experience delivered in Virtual Reality (VR) or Script-Driven Imagery (SDI). Methods: In a randomised controlled crossover design, differences in the induced analogue trauma symptoms between multi-sensory analogue trauma by either VR or SDI versus a neutral condition were assessed in 127 non-clinical participants. Results: Analogue symptoms (psychophysiological responses, coping behaviour and intrusive memories of the experimental trauma) increased following analogue trauma in both VR and SDI, with more analogue symptoms for VR. Psychophysiological arousal was in general higher in VR. Limitations: The analogue trauma situation of a car park fire that was used may be infrequent in real life. Conclusions: Multisensory (vision, olfaction, hearing) analogue trauma in VR and SDI offers a useful tool for the induction and real-time assessment of peri- and post-traumatic risk factors for analogue stress-associated psychopathology. VR was more effective in inducing analogue symptoms than SDI, even though the latter might be more personalised. New experimental models for studying trauma exposure and responses may contribute to a better understanding of risk factors and help to identify and protect individuals at risk.